Implementation of Character Education in Students in State Schools 09 Review Tapakis - Leli Hastuti (Postgraduate School, Universitas Negeri Padang, 2019)
Characters is a imfortant aspect of the quality of Human Resources because it alsodetermines the progress of a nation. Quality characters need to be formed and fostered from a early age. Early age is a golden age but is critical for the formation of one’s characters. Forming students with characters is not easy as we flip behind our palms, but throught continous processes and effford and deep reflection to shape one’s characters. The declaration of characters education is certainly intended to be one answer to the nation’s current problems. Problems arise from various sources of educational failure in instilling. Purpose of educational is not only form intelligent and competent students but to create energies of students with strong character. This study aims to apply character education to students, supporting factors, and in hibiting factors. Research is qualitative descriptive. Data collection through interviews, observation, and documentation data. The technique of checking the validity of the data uses source and technique triangulation. The result showed that (1) The application of character integration in the learning process, habituation activities, exemplary, education in extracurricular activities such as pramuka, and creates character books for low class and high class. The character values instilled are religius, nationalist, independent, mutual cooperation, and integrated. (2) supporting factors namely the desire of students who want to change, collaborate with parents/committees schools, collaboration between teachers, collaboration between teachers and principals, as well as collaboration with SD N 09 Ulakan Tapakis with PT. TRAKINDO BUILDING THE NATION CHARACTERS took place since the aftermath of the 30 Septmber 2009 earthquake untill now. (3) Inhibiting factors namely students, environmental condition that do not support, the teachers supervision oversight, and lack of supervision from parents. Keyword: implementation, character education, learning